Perovskite surface defect passivation material, passivation unit, preparation method and battery
By using hindered Lewis acid-base pairs as passivation materials on the surface of perovskite solar cells, the stability and efficiency problems of perovskite solar cells have been solved, the fabrication process has been simplified, the cost has been reduced, and they are suitable for large-scale production, especially performing well in high temperature and high humidity environments.
Patent Information
- Application Number
- CN202411394953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
Existing perovskite solar cells suffer from poor stability, and the interface layer materials cannot effectively suppress interfacial charge recombination, resulting in low efficiency. Furthermore, the fabrication methods are complex and costly, making them unsuitable for large-scale production.
By using hindered Lewis acid-base pairs as passivation materials, a passivation layer is formed on the surface of the perovskite layer through spin coating, which inhibits charge recombination between the perovskite and the electron transport layer, thereby improving stability and efficiency.
The process of preparing the passivation layer is simplified, production costs are reduced, it is suitable for large-scale production, and the stability and efficiency of perovskite photovoltaic devices are significantly improved in high temperature and high humidity environments.
Smart Images

Figure CN119300612A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and specifically provides a perovskite surface defect passivation material, a passivation unit, a preparation method and a battery. Background Art
[0002] Since perovskite solar cells first achieved a photoelectric conversion efficiency of 3.8% in 2009, perovskite materials have become a hot semiconductor material, with the highest photoelectric efficiency exceeding that of silicon cells, reaching 26.1%. The poor stability and short life of perovskite solar cells have always restricted their commercial development. Therefore, how to improve the stability of perovskite solar cells is still a key issue that needs to be solved in the process of their industrialization.
[0003] In the traditional method for preparing perovskite thin films, the perovskite thin films prepared by the solution method usually contain a large number of grain boundary defects, which cause water and oxygen in the air to penetrate into the perovskite through these defects, thereby causing the perovskite to decompose. At the same time, due to the unstable energy of the interface defects, it is easily destroyed by external factors (such as light, electric field, heat, etc.), which will also accelerate the decomposition of the perovskite. In order to improve the stability problem, some solutions have been adopted in the prior art. For example, by adding additives to the perovskite precursor liquid, adjusting the perovskite components, improving the encapsulation technology, etc., the stability problem can be alleviated to a certain extent. Although the prior art has solved the problem of perovskite solar cells to a certain extent, there are still some problems and shortcomings. First, the existing interface layer materials may not be able to effectively suppress the interface charge recombination, resulting in low efficiency of the battery. Secondly, the existing interface layer materials may have a negative impact on the stability of the perovskite and affect the long-term performance of the battery. In addition, the existing interface layer preparation method is complicated and costly, which is not conducive to large-scale production. In addition, under high humidity and high humidity conditions, unencapsulated perovskite solar cells still have low stability and low photoelectric conversion efficiency. Therefore, how to reduce the grain boundary defects of perovskite and improve the efficiency and stability of perovskite photovoltaic devices has become a problem that needs to be solved urgently. Summary of the invention
[0004] In order to overcome the above-mentioned defects, the present invention proposes a perovskite surface defect passivation material, a passivation unit, a preparation method and a battery. The use of the passivation material of the present invention can improve the environmental tolerance of the battery, while effectively passivating the surface defects of the perovskite battery and improving the stability of the perovskite photovoltaic device.
[0005] In a first aspect, the present invention provides a perovskite surface defect passivation material, comprising: a hindered Lewis acid-base pair.
[0006] Furthermore, in the hindered Lewis acid-base pair, the molar ratio of the Lewis acid to the Lewis base is (0.5-2):1 or the molar ratio of the Lewis base to the Lewis acid is (0.5-2):1.
[0007] Furthermore, in the hindered Lewis acid-base pair, the molar ratio of Lewis acid to Lewis base is 1:1.
[0008] Furthermore, the hindered Lewis acid-base pair includes one or more of tBu3P / B(C6F5), tBu3P / Al(C6F5)3, Mes3P / B(C6F5)3 and Mes3P / Al(C6F5)3.
[0009] Furthermore, the hindered Lewis acid-base pair includes (tBu3P / B(C6F5)3 and (tBu3P / Al(C6F5)3, and the molar ratio of the two is 1:1.
[0010] In a second aspect, the present invention provides a passivation unit for a perovskite battery, comprising:
[0011] Perovskite layer;
[0012] The passivation layer is obtained according to the passivation material described in the first aspect.
[0013] In a third aspect, the present invention provides a method for preparing a passivation unit of a perovskite battery, comprising:
[0014] Forming a perovskite layer;
[0015] Prepare a passivation layer solution according to the passivation material of the first aspect;
[0016] A passivation layer is formed on the perovskite layer using the passivation layer solution.
[0017] Furthermore, the preparation method of the passivation layer solution includes:
[0018] The passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution.
[0019] Furthermore, the concentration of the passivation layer solution is 0.1-2 mg / mL.
[0020] Furthermore, the solvent includes at least one of propanol and chloroform.
[0021] Further, the forming a passivation layer on the perovskite layer using the passivation layer solution comprises:
[0022] The passivation layer solution is spin-coated on the perovskite layer to form the passivation layer.
[0023] Further, the spin coating of the passivation layer solution on the perovskite layer comprises:
[0024] The passivation layer solution was spin coated on the perovskite layer at 3000-5000 rpm for 20-60 s.
[0025] Further, after the step of spin coating the passivation layer solution on the perovskite layer, the method further comprises:
[0026] Anneal at a preset temperature.
[0027] Further, the annealing at a preset temperature includes:
[0028] Anneal at 80-150°C for 0.1-1 hour.
[0029] In a fourth aspect, the present invention provides a perovskite battery, comprising:
[0030] substrate;
[0031] A first electrode formed on the substrate;
[0032] a first transmission layer formed on the first electrode;
[0033] The passivation unit according to the second aspect, wherein the perovskite layer is arranged close to the first transmission layer;
[0034] a second transmission layer formed on the passivation unit;
[0035] The second electrode is formed on the second transmission layer.
[0036] Furthermore, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.
[0037] The above one or more technical solutions of the present invention have at least one or more of the following beneficial effects:
[0038] In the technical solution of the present invention, hindered Lewis acid-base pairs (FLP) are used as the interface layer material, which can effectively passivate the perovskite surface and inhibit charge recombination at the interface between the perovskite and the electron transport layer, thereby improving the efficiency of the perovskite photovoltaic device.
[0039] The present invention performs well in improving the environmental tolerance of the battery, especially in high temperature and high humidity environments, the stability of the battery is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The disclosure of the present invention will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In addition, similar numbers in the figures are used to represent similar components, among which:
[0041] Figure 1 It is a schematic flow chart of main steps of a method for preparing a passivation unit of a perovskite battery according to one embodiment of the present invention;
[0042] Figure 2 It is a schematic diagram of the main structure of a perovskite battery according to an embodiment of the present invention.
[0043] Reference numerals list :
[0044] 1: substrate; 2: first electrode; 3: first transmission layer; 4: perovskite layer; 5: passivation layer; 6: second transmission layer; 7: second electrode. DETAILED DESCRIPTION
[0045] Some embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0046] The invention provides a perovskite surface defect passivation material, comprising: a hindered Lewis acid-base pair.
[0047] The hindered Lewis acid-base pairs are called “Frustrated Lexis Pairs” in English, abbreviated as FLPs, and are also translated as “mismatched Lewis” and “space-constrained Lewis acid-base pairs”. The present invention adopts the translation of “hindered Lewis acid-base pairs”.
[0048] Since their breakthrough discovery by Ste Phan's research group, hindered Lewis acid-base pairs have been used primarily in the field of catalysis technology.
[0049] Through in-depth research, the inventors found that the hindered Lewis acid-base pair can interact with the defects on the surface of the perovskite, which not only effectively passivates these defects but also improves the stability of the perovskite battery, especially its tolerance in high temperature and high humidity environments. This discovery not only improves the photoelectric conversion efficiency of the perovskite battery, but also significantly increases the battery's service life.
[0050] In one embodiment, in the hindered Lewis acid-base pair, the molar ratio of Lewis acid to Lewis base is (0.5-2):1 or the molar ratio of Lewis base to Lewis acid is (0.5-2):1.
[0051] In one embodiment, in the hindered Lewis acid-base pair, the molar ratio of Lewis acid to Lewis base is 1:1.
[0052] In one embodiment, the hindered Lewis acid-base pair includes one or more of tBu3P / B(C6F5), tBu3P / Al(C6F5)3, Mes3P / B(C6F5)3 and Mes3P / Al(C6F5)3.
[0053] In the case of a combination of multiple components, in one embodiment, the hindered Lewis acid-base pair includes tBu3P / B(C6F5) and tBu3P / Al(C6F5)3; wherein the molar ratio of tBu3P / B(C6F5) and tBu3P / Al(C6F5)3 is 1:1.
[0054] The present invention also provides a passivation unit for a perovskite battery, comprising:
[0055] Perovskite layer;
[0056] The passivation layer is obtained according to the passivation material.
[0057] The present invention uses a hindered Lewis acid-base pair as a passivation material, and utilizes the hindered Lewis acid-base pair to react with the non-coordinated Pb in the perovskite. 2+ The multiple effects of perovskite components such as iodide ions and ammonium salts can reduce the grain boundary defects of perovskite and improve the efficiency and stability of perovskite photovoltaic devices.
[0058] By applying hindered Lewis acid-base pairs to the surface defect passivation treatment of perovskite cells, the present invention provides new possibilities for the commercial application of perovskite cells. This innovative technology provides new ideas and methods for the improvement and application of perovskite cell performance.
[0059] The present invention also provides a method for preparing a passivation unit of a perovskite battery, referring to Figure 1 ,include:
[0060] S1, formation of perovskite layer;
[0061] S2, preparing a passivation layer solution according to the passivation material;
[0062] S3, forming a passivation layer on the perovskite layer using the passivation layer solution.
[0063] The preparation process of the passivation unit of the present invention is very simple and does not require complex experimental devices and equipment. The entire preparation process does not require harsh and high energy consumption conditions, thereby greatly reducing production costs and energy consumption. This simple preparation method is very conducive to large-scale promotion and application, and can effectively realize industrial production, thereby meeting market demand and improving production efficiency.
[0064] In one embodiment, in step S2, the method for preparing the passivation layer solution includes:
[0065] The passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution.
[0066] In one embodiment, the concentration of the passivation layer solution is 0.1-2 mg / mL.
[0067] In one application scenario, the concentration of the passivation layer solution is 2 mg / mL.
[0068] In a specific embodiment, the selected solvent should have the ability to effectively dissolve the components of the hindered Lewis acid-base pair. In this way, when the hindered Lewis acid-base pair is dissolved in the solvent, a uniform and stable system can be formed. The selection of such a solvent is crucial for the smooth progress of the entire passivation process.
[0069] Optionally, the solvent comprises at least one of chloroform and propanol. The propanol may be isopropanol.
[0070] Due to their unique chemical properties, these solvents can ensure that the hindered Lewis acid-base pairs are fully dissolved in the solvent, thereby forming a stable system and providing favorable conditions for subsequent interfacial passivation.
[0071] In one embodiment, in step S3, forming a passivation layer on the perovskite layer using the passivation layer solution comprises:
[0072] S31, spin coating the passivation layer solution on the perovskite layer;
[0073] S33, forming the passivation layer.
[0074] In one embodiment, spin coating the passivation layer solution on the perovskite layer comprises:
[0075] The passivation layer solution was spin coated on the perovskite layer at 3000-5000 rpm for 20-60 s.
[0076] In one application scenario, the passivation layer solution is spin-coated on the perovskite layer at 5000 rpm for 35 seconds.
[0077] In one embodiment, after the step S31 of spin coating the passivation layer solution on the perovskite layer, the method further comprises:
[0078] S32, annealing at a preset temperature.
[0079] In one embodiment, in step S32, the annealing at a preset temperature includes:
[0080] Anneal at 80-150°C for 0.1-1 hour.
[0081] The present invention also provides a perovskite battery, referring to Figure 2 , including: a substrate 1, a first electrode 2, a first transmission layer 3, a perovskite layer 4, a passivation layer 5, a second transmission layer 6 and a second electrode 7.
[0082] The specific structure is as follows:
[0083] The first electrode 2 is formed on the substrate 1 .
[0084] The first transmission layer 3 is formed on the first electrode 2 .
[0085] The passivation unit is the above-mentioned passivation unit. In addition, the passivation unit can also be a passivation unit prepared by the above-mentioned preparation method.
[0086] The passivation unit includes a perovskite layer 4 and a passivation layer 5; wherein the perovskite layer 4 is also called a perovskite light absorbing layer and is disposed close to the first transmission layer 3, and the passivation layer 5 is disposed close to the second transmission layer.
[0087] The second transmission layer 6 is formed on the passivation unit, specifically, on the passivation layer 5 .
[0088] The second electrode 7 is formed on the second transmission layer 6 .
[0089] In one embodiment, the first transport layer 3 is a hole transport layer, and the second transport layer 6 is an electron transport layer.
[0090] In one embodiment, the battery further includes a hole blocking layer, wherein the hole blocking layer is formed between the electron transport layer and the second electrode.
[0091] In one embodiment, the substrate 1 is a conductive glass layer, such as ITO or TCO glass.
[0092] The material of the electron transport layer is selected from [6,6]-phenyl-C61-butyric acid methyl ester, C 60 and tin oxide.
[0093] The material of the perovskite layer 4 includes a first perovskite material and a second perovskite material;
[0094] The first perovskite material is selected from at least one of lead halide salts and tin halide salts, and the second perovskite material is selected from at least one of formamidine halide salts, methylamine halide salts and cesium halide salts.
[0095] In one embodiment, the mass ratio of the first perovskite material to the second perovskite material is (0.9-1.2):1.
[0096] The material of the hole blocking layer is selected from 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or zirconium acetylacetonate.
[0097] The second electrode 7 is a metal electrode.
[0098] The metal electrode is selected from at least one of silver, copper, conductive oxide and carbon electrodes.
[0099] In combination with the examples below, hindered Lewis acid and base are used as passivation materials to prepare perovskite cells, and the cell performance is tested.
[0100] Example 1
[0101] Step 1: ultrasonically clean the substrate TCO conductive glass with deionized water, acetone and isopropanol for 15 minutes respectively, and finally put it into a drying oven to dry at 75°C for use; put the dried TCO glass substrate into a UV ozone machine for 5 minutes to remove organic impurities on its surface and optimize its surface wettability.
[0102] Step 2: Dissolve 1 mg of 2PACz in 2 mL of chlorobenzene and stir at room temperature until completely dissolved to obtain an organic hole transport material solution.
[0103] Step 3: Take 30uL of the organic hole transport material solution prepared in step 2, drop it on the TCO glass treated in step 1, spin coat it at 5000rpm for 30s, and heat and anneal it at 100℃ on a hot stage for 10min to form a hole transport layer.
[0104] Step 4: Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF), and stir at room temperature until completely dissolved to obtain a perovskite precursor solution.
[0105] Step 5. In a nitrogen glove box, take 30 μL of perovskite precursor solution and add it to the TCO conductive glass that forms the hole transport layer. First, spin coat it at 1000 rpm for 10 seconds, and then spin coat it at 5000 rpm for 30 seconds. During this process, 125 μL of chlorobenzene is quickly added after 25 seconds. Then, the TCO glass is placed on a hot stage and heated and annealed at 100°C for 40 minutes to form a 500 nm perovskite layer.
[0106] Step 6: Dissolve 2.0 mg of the hindered Lewis acid-base pair (tBu3P / B(C6F5)) in 1 mL of isopropanol and stir at room temperature to obtain the passivation layer solution of Example 1. In the hindered Lewis acid-base pair of this example, the molar ratio of the Lewis base to the Lewis acid is 1:1.
[0107] Step 7: Take 75 uL of the passivation layer solution obtained in step 6 and drop it onto the top of the perovskite layer, spin-coat it at 5000 rpm for 35 seconds, and then anneal it at 100° C. for 0.8 hours to form a passivation layer.
[0108] Step 8: Dissolve 20 mg of methanefullerene phenyl-C61-butyric acid methyl ester (PCBM) in 1 mL of chlorobenzene and stir at room temperature to obtain [6,6]-phenyl-C61-butyric acid methyl ester solution.
[0109] Step 9: Take 30uL of the [6,6]-phenyl-C61-butyric acid methyl ester solution prepared in step 8 and drop it on the TCO conductive glass with the passivation layer, and spin coat it at 3000rpm for 60s to form an electron transport layer.
[0110] Step 10: Transfer the TCO conductive glass with the electron transport layer, passivation layer, perovskite layer and hole transport layer to the vacuum coating instrument and wait until the vacuum degree is 3*10 -4 A silver electrode was evaporated at 100 nm in thickness to obtain an electrode layer.
[0111] Example 2
[0112] The difference between Example 2 and Example 1 is that:
[0113] (1) In step 6, 2.0 mg of hindered Lewis acid-base pair tBu3P / Al(C6F5)3 was dissolved in 2 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Example 2.
[0114] (2) In step 7, 75 uL of the passivation layer solution obtained in step 6 was dripped onto the top of the perovskite layer, spin-coated at 3000 rpm for 20 seconds, and then annealed at 150° C. for 0.3 hours to form a passivation layer.
[0115] The other steps are the same as those in Example 1.
[0116] Example 3
[0117] The difference between Example 3 and Example 1 is that:
[0118] (1) In step 6, 1.0 mg of hindered Lewis acid-base pair Mes3P / B(C6F5)3 was dissolved in 2 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Example 3.
[0119] (2) In step 7, 75 uL of the passivation layer solution obtained in step 6 was dripped onto the top of the perovskite layer, spin-coated at 4000 rpm for 50 s, and then annealed at 80° C. for 1 hour to form a passivation layer.
[0120] The other steps are the same as those in Example 1.
[0121] Example 4
[0122] The difference between Example 4 and Example 1 is that:
[0123] (1) In step 6, 2.0 mg of hindered Lewis acid-base pair Mes3P / Al(C6F5)3 was dissolved in 1 mL of chloroform and stirred at room temperature to obtain the passivation layer solution of Example 4.
[0124] (2) In step 7, 75 uL of the passivation layer solution obtained in step 6 was dripped onto the top of the perovskite layer, spin-coated at 3500 rpm for 60 s, and then annealed at 140° C. for 0.1 hour to form a passivation layer.
[0125] The other steps are the same as those in Example 1.
[0126] Example 5
[0127] The difference between Example 5 and Example 1 is that:
[0128] (1) In step 6, 2.0 mg of the hindered Lewis acid-base pair composition was dissolved in 1 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Example 5. The hindered Lewis acid-base pair composition includes tBu3P / B(C6F5) and tBu3P / Al(C6F5)3, which are mixed at a mass ratio of 1:1.
[0129] The other steps are the same as those in Example 1.
[0130] Example 6
[0131] The difference between Example 6 and Example 1 is that:
[0132] (1) In step 6, in the hindered Lewis acid-base pair (tBu3P / B(C6F5)), the molar ratio of Lewis base to Lewis acid is 0.5:1.
[0133] The other steps are the same as those in Example 1.
[0134] Example 7
[0135] The difference between Example 7 and Example 1 is that:
[0136] (1) In step 6, in the hindered Lewis acid-base pair (tBu3P / B(C6F5)), the molar ratio of Lewis base to Lewis acid is 2:1.
[0137] The other steps are the same as those in Example 1.
[0138] Example 8
[0139] The difference between Example 8 and Example 1 is that:
[0140] (1) In step 6, in the hindered Lewis acid-base pair (tBu3P / B(C6F5)), the molar ratio of Lewis acid to Lewis base is 0.5:1.
[0141] The other steps are the same as those in Example 1.
[0142] Example 9
[0143] The difference between Example 9 and Example 1 is that:
[0144] (1) In step 6, in the hindered Lewis acid-base pair (tBu3P / B(C6F5)), the molar ratio of Lewis acid to Lewis base is 2:1.
[0145] The other steps are the same as those in Example 1.
[0146] Comparative Example 1
[0147] The difference between Comparative Example 1 and Example 1 is that:
[0148] (1) Excluding steps 6 and 7;
[0149] (2) In step 9, 30 uL of the [6,6]-phenyl-C61-butyric acid methyl ester solution prepared in step 8 is dripped onto the TCO conductive glass having the perovskite layer formed in step 5.
[0150] The other steps are the same as those in Example 1.
[0151] Comparative Example 2
[0152] The difference between Comparative Example 2 and Example 1 is:
[0153] (1) In step 6, 2.0 mg of Lewis acid ammonium chloride was dissolved in 1 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Comparative Example 2.
[0154] The other steps are the same as those in Example 1.
[0155] Comparative Example 3
[0156] The difference between Comparative Example 3 and Example 1 is that:
[0157] (1) In step 6, 2.0 mg of Lewis base potassium acetate was dissolved in 1 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Comparative Example 2.
[0158] The other steps are the same as those in Example 1.
[0159] Comparative Example 4
[0160] The difference between Comparative Example 4 and Example 1 is that:
[0161] (1) In step 6, 2.0 mg of the composition of Lewis acid and Lewis base was dissolved in 1 mL of isopropanol and stirred at room temperature to obtain the passivation layer solution of Comparative Example 4. The composition of Lewis acid and Lewis base was ammonium chloride and potassium acetate mixed in a molar ratio of 1:1.
[0162] The other steps are the same as those in Example 1.
[0163] The above-mentioned Examples 1-5 and Comparative Examples 1-4 were subjected to electrochemical tests, and the test results are shown in Table 1.
[0164] Table 1 Test results of battery electrochemical performance of examples and comparative examples
[0165] <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) Eff(%) Example 1 24.79 1.15 82.3 23.46 Example 2 24.48 1.17 82.9 23.74 Example 3 24.32 1.16 83.5 23.56 Example 4 24.37 1.17 83.2 23.72 Example 5 24.52 1.17 82.6 23.69 Comparative Example 1 24.12 1.10 79.4 21.07 Comparative Example 2 24.09 1.14 81.1 22.28 Comparative Example 3 24.25 1.13 81.5 22.33 Comparative Example 4 24.36 1.14 82.2 22.82
[0166] It can be seen from the data in Table 1 that the present invention uses hindered Lewis acid-base pairs (FLP) as the interface layer material, which can effectively passivate the perovskite surface and inhibit charge recombination at the interface between the perovskite and the electron transport layer, thereby improving the efficiency of the perovskite photovoltaic device.
[0167] Compared with the prior art and the use of Lewis acid and / or Lewis base for passivation, the interface layer material of the present invention can more effectively solve the problem of interface charge recombination and improve the efficiency of the battery.
[0168] The interface layer preparation method of the present invention is simple, low-cost, and conducive to large-scale production. Compared with the prior art, the interface layer preparation method of the present invention is simpler, lower-cost, more suitable for large-scale production, and has higher practical value.
[0169] The stability test is then performed on the batteries of Examples 1-5 and Comparative Examples 1-4 prepared with the passivation material of the present invention.
[0170] The photoelectric conversion efficiency of the cell of the present invention was tested and normalized. The test method of the photoelectric conversion efficiency test is: the perovskite solar cell prepared in each embodiment and comparative example is tested for stability performance at 85°C. Specifically, the device is placed on a hot plate and heated at 85°C for 1200 hours before the efficiency test is performed; normalized efficiency = energy conversion efficiency after heating / energy conversion efficiency before heating × 100%, and the stability of the solar cell is tested by normalized efficiency. The test results are shown in Table 2.
[0171] Table 2 Battery stability test
[0172] Photoelectric conversion efficiency (%) Normalized efficiency Example 1 21.81 93% Example 2 21.36 90% Example 3 21.44 91% Example 4 21.34 90% Example 5 21.79 92% Comparative Example 1 9.9 47% Comparative Example 2 12.2 55% Comparative Example 3 12.7 57% Comparative Example 4 14.1 62%
[0173] It can be seen from Table 2 that the present invention can improve the stability of the battery. This is because when the hindered Lewis acid-base pair acts on the perovskite interface, various defects on the perovskite surface are effectively passivated, carrier recombination at the interface is inhibited, and the efficiency of the perovskite battery is improved.
[0174] The interface layer material of the present invention is a hindered Lewis acid-base pair, which has little effect on the stability of perovskite and is conducive to maintaining the long-term performance of the battery. Compared with the prior art, the interface layer material of the present invention can avoid negative impact on the stability of perovskite and ensure the long-term performance of the battery.
[0175] Next, the high temperature and high humidity performance (temperature 85° C., humidity 85%) of the batteries of Examples 1-5 and Comparative Examples 1-4 prepared with the passivation material of the present invention were tested after packaging.
[0176] The test process is as follows: the perovskite solar cells prepared in the embodiments and comparative examples are placed in a high temperature and high humidity aging test box, with the temperature set to 85° C. and the humidity set to 85%.
[0177] The test was carried out according to the above process and the results are shown in Table 3.
[0178] Table 3 High temperature and high humidity resistance test results
[0179] Photoelectric conversion efficiency (%) Normalized efficiency Example 1 22.75 97% Example 2 22.55 95% Example 3 22.38 95% Example 4 22.77 96% Example 5 22.98 97% Comparative Example 1 12.01 57% Comparative Example 2 16.71 75% Comparative Example 3 14.92 67% Comparative Example 4 17.57 77%
[0180] As can be seen from Table 3, the present invention performs well in improving the environmental tolerance of the battery, especially in high temperature and high humidity environments, the stability of the battery is significantly improved. This significant effect is mainly attributed to the hindered Lewis acid-base pair used in the present invention, which forms a large volume group, which can effectively block the corrosion of water vapor on the perovskite material. In addition, these groups can also effectively passivate the defects on the surface of the perovskite battery, thereby further improving the overall stability of the perovskite photovoltaic device.
[0181] In actual production and application, perovskite cells will inevitably encounter high temperature and high humidity environmental conditions. Under these conditions, temperature and humidity have a significant impact on the performance of perovskite solar cells. Specifically, when the temperature rises, the cell efficiency of perovskite solar cells tends to decrease. This is because high temperature accelerates the recombination rate of charge carriers inside the perovskite film, resulting in a decrease in cell efficiency. Similarly, humidity can also have a negative impact on the performance of perovskite solar cells. In a high humidity environment, water vapor is easily formed inside the perovskite solar cell, which hinders the transfer of charge and thus affects the performance of the cell. On the contrary, in a low humidity environment, the redox reaction rate inside the perovskite film will slow down, which will also lead to a decrease in cell efficiency.
[0182] The present invention significantly improves the battery's tolerance in high temperature and high humidity environments by effectively blocking water vapor and passivating surface defects, which is of great significance for the practical application of perovskite batteries. This improvement can not only ensure the stable operation of the battery in harsh environments, but also extend the battery's service life, thus providing strong technical support for the commercial application of perovskite photovoltaic devices.
[0183] It should be pointed out that although the various steps in the above embodiments are described in a specific order, those skilled in the art can understand that in order to achieve the effects of the present invention, different steps do not have to be performed in such an order. They can be performed simultaneously (in parallel) or in other orders. These changes are within the scope of protection of the present invention.
[0184] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A perovskite surface defect passivation material, characterized in that: include: Hindered Lewis acid-base pair.
2. The material according to claim 1, characterized in that In the hindered Lewis acid-base pair, the molar ratio of Lewis acid to Lewis base is (0.5-2):1 or the molar ratio of Lewis base to Lewis acid is (0.5-2):
1.
3. The material according to claim 2, characterized in that In the hindered Lewis acid-base pair, the molar ratio of Lewis acid to Lewis base is 1:
1.
4. The material according to claim 1, characterized in that The hindered Lewis acid-base pair includes one or more of tBu3P / B(C6F5), tBu3P / Al(C6F5)3, Mes3P / B(C6F5)3 and Mes3P / Al(C6F5)3.
5. The material according to claim 4, characterized in that The hindered Lewis acid-base pair includes (tBu3P / B(C6F5) and (tBu3P / Al(C6F5)3, and the molar ratio of the two is 1:
1.
6. A passivation unit for a perovskite battery, characterized in that: include: Perovskite layer; The passivation layer is obtained according to the passivation material according to any one of claims 1 to 5.
7. A perovskite battery, characterized in that: include: substrate; A first electrode formed on the substrate; a first transmission layer formed on the first electrode; The passivation unit according to claim 6, wherein the perovskite layer is arranged adjacent to the first transport layer; a second transmission layer formed on the passivation unit; The second electrode is formed on the second transmission layer.
8. The battery according to claim 7, characterized in that The first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.
9. A method for preparing a passivation unit of a perovskite battery, characterized in that: include: Forming a perovskite layer; Prepare a passivation layer solution according to the passivation material according to any one of claims 1 to 5; A passivation layer is formed on the perovskite layer using the passivation layer solution.
10. The method according to claim 9, characterized in that The preparation method of the passivation layer solution comprises: The passivation material is dissolved in a solvent and mixed evenly to obtain a passivation layer solution.
11. The method according to claim 10, characterized in that The concentration of the passivation layer solution is 0.1-2 mg / mL.
12. The method according to claim 10, characterized in that The solvent includes at least one of propanol and chloroform.
13. The method according to claim 9, characterized in that The forming of a passivation layer on the perovskite layer using the passivation layer solution comprises: The passivation layer solution is spin-coated on the perovskite layer to form the passivation layer.
14. The method according to claim 13, characterized in that The spin coating of the passivation layer solution on the perovskite layer comprises: The passivation layer solution was spin coated on the perovskite layer at 3000-5000 rpm for 20-60 s.
15. The method according to claim 13, characterized in that After the step of spin coating the passivation layer solution on the perovskite layer, the method further comprises: Anneal at a preset temperature.
16. The method according to claim 15, characterized in that The annealing at a preset temperature includes: Anneal at 80-150°C for 0.1-1 hour.